THE INFLUENCE OF AUTHENTIC LEADERSHIP, SELF EFFICACY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR ON TOTAL QUALITY MANAGEMENT (TQM) THROUGH ORGANIZATIONAL CULTURE - Siswadhi, Ferry; Liantifa, Melifia; Yelnim, Yelnim (Dinasti Publisher, 2023)
The reason for this study is to confirm the effectiveness of authentic leadership, self-efficacy, and organizational citizenship behavior on total quality management through organizational culture.. All respondents in this study were construction officers in Sungai Penuh City, Jambi Regency, Indonesia. Since the method used was full sampling method, the number of respondents obtained was 105. The information used in this study is primary information. This study uses model testing using structural equation modeling (SEM). As a result, authentic leadership, self-efficacy and OCB have a 33.5% influence on the organizational culture of structural officers in Sungai Penuh city, and authentic leadership, self-competence Self-efficacy, OCB and organizational culture have a 33.5% influence on the agency's organizational culture officers in Sungai Penuh city that it had a 75.2% impact on the Quality Management (TQM) of the Sungai Penuh City Structural Authority.